The first attempt to study the habitat-related distribution of the owlet moths (Lepidoptera: Noctuoidea) in the mountains of Central Asia using low-power UV-sources - Stanislav K. Korb (Трансформация экосистем, 2023)
For the first time, the habitat-related distribution of the owlet moths in the central part of the northern slope of the Kyrgyz Mountain Range was studied with the help of low-power UV-sources. In total, 174 species in seven types of habitats were identified: 78 species in the sagebrush-fescue steppe, 111 species, in the forb-feather grass steppe, 94, in the xerophytic meadow, 49, in the subalpine meadow and in the thickets of shrubs each, 40, in the mixed forest, and 13 species in the coniferous forest. The fauna of Noctuoidea at most stations in the study area are not similar, but the stations that are similar by conditions (both types of steppes and a xerophytic meadow, thickets of shrubs and mixed forest) are combined into clusters. The number of eurybiont species among those noted for the studied locality is 85%. The share of Central Asian endemics among stenobiont species exceeds 57%.